Bernard Shaw's Caesar and Cleopatra [videorecording (DVD)] - Pascal, Gabriel, 1894-1954; Pascal, Gabriel, 1894-1954; Shaw, Bernard, 1856-1950; Leigh, Vivien, 1913-1967; Rains, Claude, 1889-1967; Granger, Stewart, 1913-1993; Robson, Flora, 1902-1984; Parker, Cecil, 1897-1971 (Eclipse (Criterion Collection (Firm)). George Bernard Shaw on film., 2010)
Experience a lavish epic about love and politics in ancient Rome and Egypt.